2013
DOI: 10.1007/s10750-013-1649-8
|View full text |Cite
|
Sign up to set email alerts
|

Stream order-dependent diversity metrics of epilithic diatom assemblages

Abstract: Diatoms are considered as an appropriate indicator group for ecological status assessment of surface waters. These organisms can be indicative not only of the waterchemical but also of the hydromorphological characteristics (e.g., stream size, physical habitat diversity) of running waters. In this study, diatom diversity metrics (species number, Shannon diversity, and evenness) from 506 sites in Pannon ecoregion (Hungary) were compared to the Strahler stream order system established with ArcView GIS 3.2. SOM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…For example, N. palea a mobile diatom (Berthon et al, 2011) was one of the dominant species under high flow conditions in July, whereas under low flow conditions in August A. minutissima, a stalked diatom (Berthon et al, 2011) was the dominant species. Species diversity is frequently used in ecological status assessment for explaining spatial and temporal patterns of biotic communities (Borics et al, 2012;Stenger-Kovacs et al, 2014). Some studies have found that species biodiversity may increase or decrease with the increase of pollution, and it mainly depends on the degree and the type of pollution (Juttner et al, 1996;Stevenson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, N. palea a mobile diatom (Berthon et al, 2011) was one of the dominant species under high flow conditions in July, whereas under low flow conditions in August A. minutissima, a stalked diatom (Berthon et al, 2011) was the dominant species. Species diversity is frequently used in ecological status assessment for explaining spatial and temporal patterns of biotic communities (Borics et al, 2012;Stenger-Kovacs et al, 2014). Some studies have found that species biodiversity may increase or decrease with the increase of pollution, and it mainly depends on the degree and the type of pollution (Juttner et al, 1996;Stevenson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Strahler stream order, which was originally developed by geomorphologists to classify position within branching channel networks, remains a useful organizing principle for evaluating processes that occur during downstream DOM transport in rivers (Strahler 1957). Strahler stream order has been shown to be strongly correlated with a variety of metrics, including catchment drainage area (Hughes et al 2011), stream width (Downing et al 2012), air-water gas transfer velocities , and diatom diversity (Stenger-Kovács et al 2014). Since a large proportion of the catchment drains directly from first-order streams with decreasing proportions for each successively increasing stream order, Strahler stream order reflects the strength and directness of terrestrialaquatic linkages.…”
Section: Stream Order As An Organizing Principlementioning
confidence: 99%
“…While conventional methods might distortion along non-linear relationships (Giraudel and Lek, 2001), SOM is stated to be useful for exploratory data analysis in a multidimensional scale (Shanmuganathan et al, 2006). The SOM method has been already used successfully in potamoplankton ecology (Várbíró et al, 2007;Stankovi c et al, 2012); in fish zonation (Lasne et al, 2007); as well as in diatom research at large spatial scales (Rimet et al, 2004;Park et al, 2006;Stenger-Kovács et al, 2014).…”
Section: Statistical Analysesmentioning
confidence: 99%